EDUKASI PENTINGNYA SIMRS DALAM PENERAPAN REKAM MEDIK ELEKTRONIK TERINTEGRASI DI RUMAH SAKIT UMUM SEMBIRING - Wahab, Bachtiyar -; Sembiring, Alprindo; Tampubolon, Elmina; Sembiring, Efrata; Sinaga, Jon Piter (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
The objective of this community service is to increase the understanding of the role of Hospital Management Information Systems (SIMRS) and how they contribute to the implementation of integrated Electronic Medical Records (RME) in hospitals. Key stakeholders, such as medical record personnel, IT staff, and hospital management, were involved in the counseling through Focus Group Discussion (FGD). The results of the Focus Group Discussion (FGD) showed that the application of SIMRS while implementing RME improved the quality of healthcare services and operational efficiency of the hospital. Key advantages found included better interdepartmental collaboration, accurate data management, and quick and easy patient access. Stakeholders agreed that education is the best way to maximize the benefits of this system. Medical personnel require specialized training to master the use of SIMRS and RME. The final conclusion of this community service activity is that the utilization of electronic medical records at the Sembirin Hospital facility in Deli Serdang Regency will facilitate employee activities.